A study on the Socio-Economic Status and level of Cognitive, Psychomotor and Affective Domains of Sidi Tribes in Open Sea Cage Culture - P.S. Swathilekshmi, R. Narayanakumar and C. Ramachandran, (Indian Journal of Extension Education, 2018)
A study on the level of socio-economic conditions of communities/beneficiaries provides the base to formulatedevelopment plans and undertake corrective action for the posterity. The present study deals with the sociopersonal,socio-psychological and socio-economic characteristics of Sidis a primitive tribal group who arethe beneficiaries of the ambitious cage culture programme of CMFRI under the Tribal Sub-Plan. A sampleof 135 Sidi tribals consisting of 45 numbers of Sidis practicing cage culture, 45 numbers of non-practicingbeneficiaries of the tribal society and 45 numbers of Sidis who were non practicing and non-beneficiariesof society were selected using multistage random sampling method. The findings of the study revealed thatmajority of the participant beneficiaries (58.33 percent) were having high school level of education, whencompared to non-participant beneficiaries majority of whom were illiterates (55.55 percent). It could beinferred that, the participant beneficiaries had a higher average monthly income ie ` 1516.25 when comparedto non-participant beneficiaries who earned an average monthly income of ` 854.25. Majority of theparticipant beneficiaries (41.67 per cent) had medium level of knowledge in cage culture followed by(50.00 per cent) who had medium level of attitude followed by 75 per cent had medium level of perceivedskill towards cage culture.